Nepal: Impacts of the Ukraine and Global Crisis on Food Systems and Poverty - Diao, Xinshen; Dorosh, Paul; Ellis, Mia; Pal, Barun Deb; Smart, Jenny; Takeshima, Hiroyuki; Thurlow, James (2022)
Presentation prepared by Xinshen Diao, Paul Dorosh, Mia Ellis, Barun Deb Pal, Jenny Smart, Hiroyuki Takeshima, and James Thurlow, all with the International Food Policy Research Institute, Washington DC. This is part of the Global Crisis Country Series.